Collusion between two-sided platforms - Lefouili, Yassine (2020)
We study the price and welfare effects of collusion between two-sided platforms and show that they depend on whether collusion occurs on both sides or a single side of the market, and whether users single-home or multi-home. Our most striking result is that one-sided collusion leads to lower (resp. higher) prices on the collusive (resp. competitive) side if the cross-group externalities exerted on the collusive side are positive and sufficiently strong. One-sided collusion may, therefore, benefit the users on the collusive side and harm the users on the competitive side. Our findings have implications regarding cartel detection and damages actions.